PENINGKATAN HASIL BELAJAR PELAJARAN IPS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS VII C SMP NEGERI 2 - Bambang Sukoco (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2022)
This study aims to determine the increase in social studies learning outcomes after using project-based learning and student engagement in the use of project-based learning. This research was conducted at SMP Negeri 2 Sugio class VII C in the 2020/2021 academic year. The method used in this research is Classroom Action Research (PTK) which is used in two cycles. The research instruments used were observation sheets of student learning activities, observation sheets of teacher teaching activities, test questions, and documentation. The results of the study can be concluded that student learning outcomes after using the project-based learning model obtained an average student learning outcome that is more increased, namely 76.96. The increase increased by 75.86% from cycle I which was only 44.82%.